Live Vaccination Tactics: Possible Approaches for Controlling Visceral Leishmaniasis - Saljoughian, Noushin; Taheri, Tahereh; Rafati, Sima (Frontiers in Immunology, 2014)
Vaccination with durable immunity is the main goal and fundamental to control leishmaniasis. To stimulate the immune response, small numbers of parasites are necessary to be presented in the mammalian host. Similar to natural course of infection, strategy using live vaccine is more attractive in compare to other approaches. Live vaccines present the whole spectrum of antigens to the host immune system in the absence of any adjuvant. Leishmanization (LZ) was the first effort for live vaccination and currently used in a few countries against cutaneous leishmaniasis, in spite of their obstacle and safety. Then, live attenuated vaccines developed with similar promotion of creating long term immunity in the host with lower side effect. Different example of attenuated strains are generated through long-term in vitro culturing, culturing under drug pressure, temperature sensitivity and chemical mutagenesis, but none are safe enough and their revision to virulent form is possible. Attenuation through genetic manipulation and disruption of virulence factors or essential enzymes for intracellular survival are among other approaches that are intensively under study. Other designs to develop live vaccines for visceral form of leishmaniasis are utilization of live avirulent microorganisms such as Lactococcus lactis, Salmonella enterica and Leishmania tarentolae called as vectored vaccine. Apparently, these vaccines are intrinsically safer and can harbor the candidate antigens in their genome through different genetic manipulation and create more potential to control Leishmania parasite as an intracellular pathogen.